2007
DOI: 10.1002/cncr.22518
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal nodal staging of nonsmall cell lung cancer using integrated 18F‐FDG PET/CT in a tuberculosis‐endemic country

Abstract: BACKGROUNDIntegrated 18fluorine fluorodeoxyglucose (18F‐FDG) positron emission tomography/computed tomography (PET/CT) has shown somewhat variable sensitivity and specificity for mediastinal nodal staging in granulomatous disease endemic areas. The purpose of the study was to prospectively evaluate the efficacy of PET/CT for mediastinal nodal staging in nonsmall cell lung cancer (NSCLC) patients in a tuberculosis‐endemic country.METHODSProspective assessment of the diagnostic efficacy of integrated PET/CT for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
103
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 17 publications
9
103
0
Order By: Relevance
“…Inflammatory lung disease is a well-known cause of false-positive FDG accumulation in both lung parenchyme and lymph nodes, which could overstage patients with lung cancer [15,16]. Since Korea is an endemic area of tuberculosis, diagnostic accuracy of 18 F-FDG PET/CT in lung cancer staging would be lower than expected. In a recent study it has been suggested that the diagnostic accuracy of 18 F-FDG PET for mediastinal lymph node staging is not enough to replace mediastinoscopy in regions with high prevalence of inflammatory lung disease [17].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Inflammatory lung disease is a well-known cause of false-positive FDG accumulation in both lung parenchyme and lymph nodes, which could overstage patients with lung cancer [15,16]. Since Korea is an endemic area of tuberculosis, diagnostic accuracy of 18 F-FDG PET/CT in lung cancer staging would be lower than expected. In a recent study it has been suggested that the diagnostic accuracy of 18 F-FDG PET for mediastinal lymph node staging is not enough to replace mediastinoscopy in regions with high prevalence of inflammatory lung disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of 18 F-fluorodeoxyglucose positron emission tomography (FDG PET) in non-small-cell lung cancer has been proven in various clinical situations, including differential diagnosis of solitary pulmonary nodules, staging, detection of recurrence, therapeutic monitoring, planning of radiotherapy, and prognosis [1][2][3][4]. 18 F-FDG PET is known to have improved the accuracy of staging for non-small-cell lung cancer compared with the conventional imaging modality [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations